How can climate change and its interaction with other compounding risks be considered in evaluation? Experiences from Vietnam. (April 2023) - Lam, Steven; Dodd, Warren; Nguyen-Viet, Hung; Unger, Fred; Le, Trang T. H.; Dang-Xuan, Sinh; Skinner, Kelly; Papadopoulos, Andrew; Harper, Sherilee L.
While evaluations play a critical role in accounting for and learning from context, it is unclear how evaluations can take account of climate change. Our objective was to explore how climate change and its interaction with other contextual factors influenced One Health food safety programs. To do so, we integrated questions about climate change into a qualitative evaluation study of an ongoing, multi-sectoral program aiming to improve pork safety in Vietnam called SafePORK. We conducted remote interviews with program researchers ( n = 7) and program participants ( n = 23). Based on our analysis, researchers believed climate change had potential impacts on the program but noted evidence was lacking, while program participants (slaughterhouse workers and retailers) shared how they were experiencing and adapting to the impacts of climate change. Climate change also interacted with other contextual factors to introduce additional complexities. Our study underscored the importance of assessing climate factors in evaluation and building adaptive capacity in programming.